PENDIDIKAN ISLAM SEBAGAI WAHANA PEMBENTUKAN SIKAP MULTIKULTURAL - Agustin, Maulid; Asy'arie, Musa; Shobahiya, Mahasri (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to explore the role of Islamic education in shaping multicultural attitudes within Indonesia, a nation characterized by rich cultural, religious, and ethnic diversity. Although Indonesia upholds the national motto Bhinneka Tunggal Ika (Unity in Diversity), challenges such as discrimination and intolerance continue to emerge as a result of primordial and exclusivist attitudes. Islamic education holds significant potential to cultivate multicultural values such as justice, tolerance, brotherhood, and respect for social plurality by integrating these principles into both the curriculum and classroom practices. Multicultural-oriented learning in madrasahs, implemented through contextual approaches, cross-cultural studies, and value-based instruction, functions as a moral mediation space and contributes to the development of an inclusive learning culture. This includes linking Qur’anic teachings on justice and compassion to real-life social issues. Teachers of Islamic Education (PAI) play a pivotal role as role models and agents of moderation, fostering tolerance and justice through social engagement and exemplary conduct. Foundational values such as justice (‘adl), brotherhood (ukhuwwah), compassion (rahmah), and respect for human dignity (karāmah insāniyyah), derived from the Qur’an and Hadith, serve as essential pillars for building a harmonious and inclusive society.Through adaptive curriculum design and participatory teaching methods, Islamic education can effectively nurture social competencies grounded in empathy and tolerance. As a result, younger generations are better equipped to live harmoniously within a multicultural society and to strengthen national unity and social justice in Indonesia.